A new working configuration: an interpretive analysis of the coworking literature - Nakao, Breno; Mussi, Clarissa Carneiro (Contextus - Revista Contemporânea de Economia e Gestão, 2018)
This study sought to understand the theoretical scope of the concept of coworking. A systematic review of the literature and an interpretative analysis of the content of the identified articles were carried out. The conclusions of the research include: (a) coworking is a recent, not sufficiently explored concept; (b) it has been explored at different levels of analysis: as a component of creative cities or cultures, as belonging to collaborative consumption, as one among several shared workspaces and as working model divergent from traditional ones; (c) there are divergences of expectations and demands on the meaning and on the form of using coworking spaces; (d) the expected benefits of the phenomenon are not observed in all coworking spaces; (e) the collaborative construction of meanings and the formation of a community sense are important elements to the emergence of coworking benefits.